Towards global political parties - Heikki Patomäki (Ethics & Global Politics, 2011)
While the transnational public sphere has existed in the Arendtian sense at least since the mid-19th century, a new kind of reflexively political global civil society emerged in the late 20th century. However, non-governmental organisations (NGOs), advocacy groups, and networks have limited agendas and legitimacy and, without the support of at least one state, limited means to realise changes. Since 2001, the World Social Forum (WSF) has formed a key attempt in forging links and ties of solidarity among diverse actors. Although the WSF may seem a party of opinion when defined negatively against neoliberal globalisation, imperialism, and violence, in more positive ideological terms it remains a rather incoherent collection of diverse actors; while itself defined as a mere open space. There is a quest for new forms of agency such as a world political party. Various historical predecessors of global political parties, real and imagined, provide conceptual resources, useful experiences for envisaging the structure, and function of a possible planetary party-formation. H.G. Wells's ‘open conspiracy’ is a particularly important future-oriented left-democratic vision. Wells believed that only a mass movement of truly committed individuals and groups could have the power to transform the world political organisation, by creating a democratic world commonwealth. Recently, for instance, Michael Hardt and Antonio Negri have formulated similar ideas. I argue that transformative political agency presupposes a shared programme, based on common elements of a wider and deeper world-view, and willingness to engage in processes of collective will-formation in terms of democratic procedures. From this perspective, I outline a possible organisation and some substantial directions for a global political party.. The point is also to respond to the criticism of existing parties and cultivate the critical-pluralist ethos of global civil society, but in terms of democratic party-formation.